POTENSI INDUSTRI PENGOLAHAN RUMPUT LAUT MENJADI BIOETANOL - Haslianti Haslianti; Muhammad Fajar Purnama; Piliana Waode (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2016)
Seaweed is one source of foreign exchange and a source of income for coastal communities. In addition, it can be used as an ingredient of food, beverages and medicines, some of the processed seaweed such as agar-agar, alginate and carrageenan are a compound that important in the industry and the amount of carbohydrate and crude fiber contained in seaweed has the potential processed to be bioethanol. This study aims to determine the potential of seaweed cultivation, the amount of seaweed production, the characteristics of the type of seaweed as a potential feedstock into bioethanol, postharvest handling and marketing of seaweed in Buton. Research using network design method APM (Academics, Government, Society). The results showed that for the raw material and the seaweed industry still facing obstacles, especially the quality still low because of the cultivation and post-harvest handling. Nevertheless, the seaweed has been able to contribute to the welfare of local people. Additionally, seaweed Eucheuma cottonii potentially be used as the raw material of bioethanol.Keywords: Bioethanol, Seaweed, Industry, Potential